Effectiveness of Cognitive Behavioral Therapy (CBT) on Psychological Distress among Mothers of Children with Autism Spectrum Disorder: The Role of Problem-Solving Appraisal - Enas Mahrous Abdelaziz; Nourah Alsadaan; Mohammed Alqahtani; Nadia Bassuoni Elsharkawy; Marwa Mohamed Ahmed Ouda; Osama Mohamed Elsayed Ramadan; Mostafa Shaban; Evon S. Shokre (Behavioral Sciences, 2024)
Mothers of children with autism spectrum disorder (ASD) face considerable psychological distress. Cognitive behavioral therapy (CBT) has shown promise in reducing caregiver burden, but evidence in the Arab world is lacking. Problem-solving appraisal training may optimize CBT’s benefits. This study evaluated a tailored CBT program emphasizing the role of problem-solving appraisal in managing distress through the process of CBT. Sixty mothers were randomly allocated in a 1:1 ratio to either the CBT intervention group or the control group. The CBT group received 3-month sessions incorporating problem-solving appraisal training within a CBT curriculum from October 2022 to April 2023. Problem-solving techniques are focused on equipping individuals with the skills to identify, approach, and effectively resolve problems, leading to a reduction in stress levels and an improved capacity to cope with difficult situations. All mothers completed assessments of socio-demographics such as age, level of education, marital status, occupation, and adequacy of family income, the Depression Anxiety Stress Scale (DASS-21) and the Problem-Solving Inventory (PSI) before and after the program. The CBT group showed significant pre-to-post reductions in depression, anxiety, stress, and general psychological distress compared to controls (all p < 0.05). They also exhibited significant improvements in problem-solving confidence, approach-avoidance style and personal control (all p < 0.05). The customized CBT program markedly improved psychological well-being for mothers of children with ASD in Egypt. Incorporating problem-solving techniques may optimize CBT’s benefits cross-culturally. These findings have implications for the implementation of evidence-based support programs for families impacted by ASD worldwide.